Jonathan Edwards and the limits of enlightenment philosophy - Chai, Leon. (New York : Oxford University Press, 1998)
Although most often associated with Puritanism in New England, Jonathan Edwards is in many respects closer to Enlightenment rationality. In this book, Leon Chai explores the connection between Edwards and such figures as Locke, Descartes, Malebranche, and Leibniz, by an analysis of topics that serve to define the nature and limits of rationality itself. The book consists of three parts, each of which begins with a detailed analysis of a crucial passage from a classic Enlightenment text, and then turns to a major theological work by Edwards in which the same issue is examined. This book will be of great interest to students and scholars of early American religion, Enlightenment philosophy, and eighteenth-century culture in general.
I. The Problem of Sensation. 1. The Argument for Empiricism. 2. Religious Affections -- II. Ideas, Objects, Mind. 3. Idea and Object. 4. Idealism -- III. The Ends of Causal Analysis. 5. Causation. 6. Freedom of the Will.
Includes bibliographical references (p. 159-160) and index.
Keywords: Edwards, Jonathan, -- 1703-1758.; Enlightenment -- United States; Knowledge, Theory of -- History -- 18th century; Knowledge, Theory of (Religion) -- History -- 18th century